IMPROVING STUDENTS’ PERSONAL SELF CONCEPT THROUGH ROLE PLAY TECHNIQUE IN TEACHING SPEAKING SKILL (Universitas Negeri Semarang, 2015)
The purpose of the research is to investigate whether role play technique can improve students’ personal self concept in teaching speaking. The method of this research was classroom action research (CAR). It was conducted in three cycles where the students of the State Institute Islamic Studies Syekh Nurjati Cirebon in the Fourth Semester of the Academic year of 2013/2014 as subjects of research consisted of 30 students. There are four kinds of instrument used in collecting the data; those are observation sheets, field notes, questionnaire and speaking prompt. The findings of the research showed that role play technique can improve students’ personal self concept in teaching speaking significantly from first cycle to the next cycle. The other finding can be seen from classroom situations, i.e.: during the speaking class the students has courage to express their idea freely, good attention in speaking class, well in discussion term, well in team work, they feel confident with their ability in solving problem, and more creative.